The Role of Hypoxia in Improving the Therapeutic Potential of Mesenchymal Stromal Cells. A Comparative Study From Healthy Lung and Congenital Pulmonary Airway Malformations in Infants - Silvestro, Serena; Diomede, Francesca; Chiricosta, Luigi; Zingale, Valeria Domenica; Marconi, Guya Diletta; Pizzicannella, Jacopo; Valeri, Andrea; Avanzini, Maria Antonietta; Calcaterra, Valeria; Pelizzo, Gloria; Mazzon, Emanuela (Frontiers in Bioengineering and Biotechnology, 2022)
Mesenchymal stromal cells (MSCs) play an important role in the field of regenerative medicine thanks to their immunomodulatory properties and their ability to secrete paracrine factors. The use of MSCs has also been tested in children with congenital lung diseases inducing fibrosis and a decrease in lung function. Congenital malformations of the pulmonary airways (CPAM) are the most frequently encountered lung lesion that results from defects of early development of airways. Despite the beneficial properties of MSCs, interventions aimed at improving the outcome of cell therapy are needed. Hypoxia may be an approach aimed to ameliorate the therapeutic potential of MSCs. In this regard, we evaluated the transcriptomic profile of MSCs collected from pediatric patients with CPAM, analyzing similarities and differences between healthy tissue (MSCs-lung) and cystic tissue (MSCs-CPAM) both in normoxia and in cells preconditioned with hypoxia (0.2%) for 24 h. Study results showed that hypoxia induces cell cycle activation, increasing in such a way the cell proliferation ability, and increase cell anaerobic metabolism in both MSCs-lung and MSCs-CPAM-lung. Additionally, hypoxia downregulated several pro-apoptotic genes preserving MSCs from apoptosis and, at the same time, improving their viability in both comparisons. Finally, data obtained indicates that hypoxia leads to a greater expression of genes involved in the regulation of the cytoskeleton in MSCs-lung than MSCs-CPAM.